Saliva sampling of alcoholic participants using three saliva collection methods - Khan, S.S.; Jameel, R.A.; Razak, F.A.; Bakri, M.M. (Penerbit Universiti Kebangsaan Malaysia, 2018)
The potential of using saliva as a diagnostic fluid is well documented. The aim of this study was to assess the quality and quantity of saliva DNA of alcoholic and non-alcoholic participants using three saliva collection methods; DNA-SalTM (Oasis Diagnostics, USA), Oragene-DNA (DNA Genotek Inc, Ontario, Canada) and whole saliva collection method. Saliva DNA of non-alcoholic (n=30) and alcoholic participants (n=10) age between 25 and 35 years was assessed qualitatively and quantitatively using spectrophotometry. Saliva DNA quantity was the highest for all participants when using the DNA-Sal TM saliva collection kit (p<0.05). The use of a mechanical scraper provided only in the DNA-Sal TM kit may have contributed to the highest DNA yield for all participants. The quantity of saliva DNA when assessed using spectrophotometer was found to be significantly lower (p<0.05) for the alcoholic (16±3.57 ng/μL) than non-alcoholic participants (19.92±6.18 ng/μL). To determine the integrity of the DNA samples, PCR amplification of the Alcohol Dehydrogenase gene, ADH1B was carried out and the PCR was found to be successful. For all participants, the DNA quality of the saliva collected using the three saliva collection methods was found to be in the acceptable range considered as pure DNA. The DNA quality and quantity of saliva collected from the three saliva collection methods were considered suitable for research purposes.